Impact factors model of internet adoption and use: taking the college students as an example (Global Journal of Human-Social Science, 2011)
The goal of this study was to explore the impacts of factors model of internet adoption along with discussing the impact of the variables on internet adoption time internet use time and internet use related to study and work This study comes up with the hypothesis based on the theoretical frameworks of diffusion of innovation uses and gratifications technology acceptance model Through taking XX university s students as sample N 302 the article reveal that socio-economic status significantly influences the time of internet adoption and use The adoption time of the internet significantly influences the time of internet use However the adoption and time usage of the internet do not significantly influence the internet use related to study and work as it is significantly affected by the college students perception about the usability and ease of use of the internet
Keywords: the adoption of the Internet；Internet use; innovation diffusion; uses and gratification; technology acceptance model